2009
DOI: 10.1063/1.3168429
|View full text |Cite
|
Sign up to set email alerts
|

Carrier localization in GaBiAs probed by photomodulated transmittance and photoluminescence

Abstract: The carrier localization phenomenon has been investigated for GaBiAs by photomodulated transmittance (PT) and photoluminescence (PL). In the case of PT measurements, a decrease in the energy-gap related PT signal has been clearly observed below 180 K. In PL spectra a broad emission band very sensitive to the excitation power has been found. In comparison to the energy-gap related transition, this band is shifted to red. The recombination time for this band at low temperature decreases from 0.7 to 0.35 ns with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
53
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 33 publications
9
53
1
Order By: Relevance
“…For both experimental conditions, it was observed that the magnetic shift is very small (about 5 meV at 15T) which evidences important localization of excitons due to disorder effects, even for the condition where the PL is dominated by free excitons. It has been previously reported that this localization of carriers is mainly due to 6 composition variation and cluster formation [3,4]. In addition, an anomalous negative magnetic shift as function of magnetic field was observed for higher temperatures (Figure 2(b)), which evidences important changes in the excitonic reduced mass.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…For both experimental conditions, it was observed that the magnetic shift is very small (about 5 meV at 15T) which evidences important localization of excitons due to disorder effects, even for the condition where the PL is dominated by free excitons. It has been previously reported that this localization of carriers is mainly due to 6 composition variation and cluster formation [3,4]. In addition, an anomalous negative magnetic shift as function of magnetic field was observed for higher temperatures (Figure 2(b)), which evidences important changes in the excitonic reduced mass.…”
Section: Resultsmentioning
confidence: 70%
“…This effect can also be evidenced by measuring the light scattering with specific polarization geometries. [1][2][3][4][5][6][7][8][9][10] are their polarizations relative to crystal planes of samples. According to the Raman selection rules for crystals for zinc-blend structures, the LO peak is allowed in -z(y,y)z geometry and forbidden in z(x,y)-z.…”
Section: Ii-experimental Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In GaAsBi alloys, the carrier localization is a well-known phenomenon, and the so called S-shape behavior can be seen in the temperature dependent PL under the low excitation conditions. 23,24 In addition, Baranowski et al 25,26 found that the PL kinetics are strongly influenced by the band bending effects as well as the carrier localization effects in type II GaAsSb/GaAs QWs using a time-resolved PL spectroscopy, suggesting that further investigations of the carrier localization phenomena in this InGaAs/GaAsBi QW are needed to evaluate its quality and perspectives for device applications. We believe that the underlying mechanism of the observations results from the band bending effect, which is intrinsic for the type-II band alignment of In 0.2 Ga 0.8 As/ GaAs 0.96 Bi 0.04 heterojunction, similar to the cases of GaAs/ GaAsSb 19 and InGaAs/GaAsSb.…”
mentioning
confidence: 99%